1987
DOI: 10.1093/infdis/155.5.897
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Clearance of Cytomegalovirus-Specific IgG After Repeated Intravenous Infusions of Human Immunoglobulin into Allogeneic Bone Marrow Transplant Recipients

Abstract: We studied the kinetics of the disappearance of CMV-specific IgG from the serum of 18 allogeneic bone marrow transplant recipients who were receiving repeated intravenous infusions of immunoglobulin. Peak serum titers occurred 24-48 hr after infusion. The mean half-life of IgG to CMV varied from 30 to 70 hr. Additional studies showed that this unexpectedly short half-life was not specific for either the preparation used or the type of patient studied. Repeated treatment did not prevent patients from developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 0 publications
4
23
0
Order By: Relevance
“…After administration of the hyperimmunoglobulin, half-life is reduced to about 1-2 days. This corresponds to the findings of Hagenbeek et al [6], who investigated two different anti-CMV hyperim munoglobulin preparations. Principally, the type of hyper immunoglobulin used seems to be the major criterion, this being valid not only for the relative content of IgG sub classes but also for the qualitative differences as related to the content of antibodies and VN titre, respectively [5], Summarizing the findings of our study and the results reported in the literature yields a non-uniform pattern of the kinetics of anti-CMV hyperimmunoglobulins.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…After administration of the hyperimmunoglobulin, half-life is reduced to about 1-2 days. This corresponds to the findings of Hagenbeek et al [6], who investigated two different anti-CMV hyperim munoglobulin preparations. Principally, the type of hyper immunoglobulin used seems to be the major criterion, this being valid not only for the relative content of IgG sub classes but also for the qualitative differences as related to the content of antibodies and VN titre, respectively [5], Summarizing the findings of our study and the results reported in the literature yields a non-uniform pattern of the kinetics of anti-CMV hyperimmunoglobulins.…”
Section: Resultssupporting
confidence: 91%
“…While the problem was originally tackled in a strictly empirical way, a few authors have recently investigated the qualitative differences between the anti-CMV immunoglo bulins presently available or have conducted pharmacoki netic studies of hyperimmunoglobulins following intrave nous administration [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In investigations using mouse-human chimeric antibodies, half-lives werecomparable to thoseofthe twoantibodies used day of study in our study [11]. Although human IgG has been reported as beingeliminated muchmore slowly thanSDZ89-104 and 89-109witha {j half-life of20 days, thehalf-lives ofCMV-specific IgG measured after treatment of BMT recipients with anti-CMV hyperimmunoglobulin were similar to those observed with SDZ 89-109 and 89-104 [12,13]. Two mechanisms mightcontributeto the acceleratedclearance of both the CMV-specific monoclonal antibodies and CMV-specific IgG in BMT patients: First, such patients are in a highly catabolic state during the posttransplant period and accelerated elimination mighttherefore merelyreflect enhanced protein turnover [14].…”
Section: Discussionsupporting
confidence: 74%
“…Unfortunately, each of these modifications reduced important antibody activities (Pollack 1983;Kim et al 1986;Bender and Hetherington 1987;Steele and Steele 1989) and shortened the half-lives of some antibodies (Janeway et al 1968;Winston et al 1982;Hagenbeek et al 1987Hagenbeek et al -1928. Today most commercial IVIGs are produced by first using Cohn cold ethanol fractionation followed by (Turner, 1989).…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%